CTPS: HAND WASHING FACILITIES USING CREATIVE SOAP TO INCREASE COMMUNITY AWARENESS ABOUT THE IMPORTANCE OF HEALTH IN BANGKA VILLAGE THROUGH MANGGARAI BARAT - Emilianus Jehadus; Eufrasia Jeramat; Maria Vilkanova Yolenta; Natalia Geofani; Regina Heni Jelita (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The CTPS (Washing Hands with Soap) program was a flagship program from Bangka Village which was created to succeed a West Manggarai government program, namely the STBM (Community-Based Total Sanitation) program. Based on the results of field observations, it appears that the health of the community in Bangka through Village was still very poor. In the sense that the community has not realized the importance of cleanliness and health. In this case, people did not care to wash their hands before eating or after doing housework that makes hands dirty. According to the health department, people in this village should know how to wash their hands properly with soap and water. For this reason, the solution is to present the PKM implementation team to carry out socialization after making the CTPS container by providing an understanding of people's habits of not washing their hands before preparing food, before eating, after defecating, after returning from the fields/gardens, after the children play with the soiland improper hand washing. In implementing this program, the TIM used a method that contains the following stages: (1) Planning of activities to be carried out, (2) Preparation of activities starting with coordinating the Village head and RT head, (3) Implementation of activities, (4) Monitoring and evaluation of activities is carried out. The results show that the people of Bangka Village have begun to realize the importance of health and hygiene and that the community has started to get used to and family members to wash their hands before eating and after urinating and defecating